Propagation of Elaeocarpus ganitrus by Air Layering - Bhojvaid, P. P.; Negi, Seema (Indian Forester, 2003)
The effects of seasons and rooting hormone on air layering were investigated in Elaeocarpus ganitrus (Rudraksha). Trials were conducted in three different seasons , viz. premonsoon , monsoon and post-monsoon using Indole Butyric Acid (IBA) as the rooting hormone (control , 100 , 250 and 500 mg l-1). Results reveal that IBA enhanced the root initiation and induced rooting in a shorter duration. Air layering trials in pre-monsoon season under 500 mg 1-l) treatment exhibited maximum rooting percentage followed by monsoon and post-monsoon season under 500 mg l-1 IBA treatment. Profuse rooting was observed in air layers treated with IBA in pre monsoon season. The callused and rooted air layers after detachment from the mother plants were transplanted separately in polyethylene bags in three different growing media [M1 - Sand , Nursery soil and Farmyard manure (1 : 2 : 1) , M2 - Sand and Nursery soil (1 : 1) and M3 - Nursery soil] under nursery conditions. A highly significant variation (P < 0.05) was observed within the effect of season and callus formation as well as root initiation. Maximum survival of callused and rooted air layers (air layering conducted in Pre-monsoon season) was observed in the growing medium containing Sand , Nursery soil and Farmyard manure (1 : 2 : 1).